Alla ricerca di luce e chiarezza: L'epistolario Helmut Lachenmann - Luigi Nono (1957-1990) - De Benedictis, Angela Ida; Mosch, Ulrich (Italy Institutio per la musica, 2012)
The volume contains more than one hundred and twenty letters exchanged between two great personalities of contemporary music. Published in the original language, the epistolary is reconstructed in its entirety and is accompanied by three Appendices that collect further letters to other personalities of the second half of the 20th century and seven texts by Lachenmann on Nono (mostly unpublished) written between 1957 and 1974.
Keywords: Lachenmann, Helmut -- 1935-; Nono, Luigi -- 1924-1990; Correspondence; Music history; Composer